The Influence of Synoptic Weather Types and Moisture Transport Pathways on Precipitation Isotopes in Southern Patagonia - Xia, Zhengyu; Butorovic Alvarado, Nicolas Santiago; Yu, Zicheng (My University, 2020)
We analyzed 28-year-long monthly oxygen isotope composition of precipitation (delta O-18(p)) data from Punta Arenas (Chile) on the leeward side of the Andes to understand how different synoptic weather types and moisture transport pathways influence delta O-18(p) variability in this region. Combining weather station 6 h precipitation data and atmospheric back trajectories, we found that in such a region where the atmospheric circulation pattern is dominated by very strong westerlies, an increased monthly proportion of easterly-delivered precipitation-with the air-mass trajectory path evading the influence of Andean "isotopic rain shadow" and having less rainout en route-would increase delta O-18(p). These synoptic easterlies are a result of quasi-stationary blocking-like flow that are an important but underappreciated part of regional circulation patterns and climate. In addition, synoptic easterlies are more often associated with heavy precipitation events as shown by weather station data and higher deuterium excess that indicates weaker post-condensation raindrop re-evaporation. Therefore, our analysis demonstrated the process link between the frequency of synoptic weather types characterized by blocking-like flow and temporal variations in delta O-18(p) in Southern Patagonia. We conclude that isotope proxy paleo-records in this region could provide unique insights into the behaviors and dynamics of the large-scale Southern Hemisphere Westerly Winds over long timescales.
Keywords: southern patagonia; stable isotopes; precipitation; back-trajectory; synoptic weather; moisture transport; southern hemisphere westerly winds